(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article analyzes the positive impact of properly organizing a daily routine in children’s lives on their physical, mental, and cognitive health. A daily schedule designed in accordance with a child’s age, type of activity, and physiological needs contributes to the formation of a healthy lifestyle, strengthens the immune system, and increases interest in learning and concentration. The article also discusses the importance of balance between sleep, nutrition, rest, and physical activity, and provides practical recommendations for parents and educators.